Impact of commercial RNA extraction methods on the recovery of human RNA sequence data from archival fixed tissues - Tess Wilson; Melanie Kuch; Debi Poinar; Jasmine Rockarts; Bruce Wainman; Susan Morgello; Hendrik Poinar (BioTechniques, 2025)
Archival fixed tissues hold key insights into the evolutionary history of RNA viruses and the associated host immune response, yet access to the RNA sequence data is limited by a lack of robust methods for RNA extraction and sequence retrieval from these tissue types. Here we compared three commercial RNA extraction techniques (bead, column, and phase-based) on five fixed human brain tissues done in triplicate, that have been stored for up to 43 years. We found that for this sample set, bead-based extractions captured longer molecules and yielded a greater proportion of unique reads when aligned to the human genome, than did column and phase-based extraction methods. Via the incorporation of multiple extraction replicates, we quantified the variability in sequencing metrics resulting from tissue sample and extraction technique heterogeneity. Additionally, we compared pre- and post-sequencing metrics and found that the former poorly predicted post-sequencing on-target success. Our findings help inform future research on the recovery of RNA from archival fixed tissues.